2022
DOI: 10.1021/acs.jpcc.2c01324
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Sensitive Vibrational Sum and Difference Frequency-Generation Spectroscopy Enabling Nanometer-Depth Profiling at Interfaces

Abstract: The unique physical and chemical properties of interfaces are governed by a finite depth that describes the transition from the topmost atomic layer to the properties of the bulk material. Thus, understanding the physical nature of interfaces requires detailed insight into the different structures, chemical compositions, and physical processes that form this interfacial region. Such insight has traditionally been difficult to obtain from experiments, as it requires a combination of structural and chemical sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…When wider probed region is required, using a novel technique to probe the nanometer scale depth profiling through the SFG and difference frequency generation spectra is available. 76 …”
Section: å-Scale Depth Information Mediated By Interfacial Dielectric...mentioning
confidence: 99%
See 1 more Smart Citation
“…When wider probed region is required, using a novel technique to probe the nanometer scale depth profiling through the SFG and difference frequency generation spectra is available. 76 …”
Section: å-Scale Depth Information Mediated By Interfacial Dielectric...mentioning
confidence: 99%
“…Finally, we note that the probed region for the depth profile where the interfacial dielectric constant varies is | z | < ∼ 2 Å at the aqueous solution interface, while the SFG active region is at least | z | < 5 Å. As such, the probed region for the depth profile is thinner than the SFG active region. When wider probed region is required, using a novel technique to probe the nanometer scale depth profiling through the SFG and difference frequency generation spectra is available …”
Section: å-Scale Depth Information Mediated By Interfacial Dielectric...mentioning
confidence: 99%
“…In addition, this method measures the average thickness of the interfacial water and not the water at a specific depth. Considering that quantitative depth information can be obtained by polarization-dependent heterodyne-detected SFG spectroscopy (PD-HD-SFG), , and phase-sensitive sum and difference frequency-generation spectroscopy (PS-SFG-DFG), the current time-resolved SFG technique combined with PD-HD-SFG or PS-SFG-DFG will endow SFG with both depth and temporal resolution, in addition to its interfacial molecule specificity.…”
Section: Discussionmentioning
confidence: 99%
“…17−19,21,22,24−28 Recently, SFG-VS has also been exploited to access quantitative depth information by investigating the interfacial dielectric profile using polarization-dependent heterodyne-detected SFG spectroscopy 32,33 and selectively determining different nonlinear interaction pathways with the combination of phase-sensitive sum and difference frequency-generation spectroscopy. 34 Here, we propose an approach to the interfacial water thickness by measuring the relaxation lifetime of the 3200 cm −1 peak using ssp polarizations. In an IR pump-SFG probe experiment, a femtosecond IR pulse is used to excite the vibration of the OH stretch mode from the ground state (ν 0 ) to its first vibrational state (ν 1 ).…”
Section: Principle For the Determination Of Interfacial Watermentioning
confidence: 99%
“…Getautis et al found that no vibrational bands could be identified in the VSFG spectrum of a 10% V1036 124 /90% C4 54 mixed SAMs, indicating a monolayer prepared from a mixed solution results in a more disordered structure compared to a monolayer from a pure V1036 solution, since the measured VSFG signal was proportional to the molecular ordering of the probed molecules . Moreover, VSFG has also been applied for studying some important aspects, including SAM growth mechanism exploration, conformational studies, and functional head design . However, the high price, few commercial resources, complex data processing, and high sample preparation requirements make VSFG not a mainstream SAM-characterization tool at present.…”
Section: Fabrication and Characterization Of The Samsmentioning
confidence: 99%